Upaya Meningkatkan Keterampilan Menulis Dengan Pendekatan Kontekstual Pada Siswa Kelas V Sekolah Dasar Negeri 2 Jambeyan, Karanganom, Klaten Tahun Pelajaran 2018/2019 - Heriyanti, Herlina (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research is motivated by the writing skills of students at the 2 Elementary Schools in Jambeyan, Karanganom Subdistrict, Klaten Regency, especially the fifth grade students are still low. As students from this school, they have not been able to demonstrate their achievements in the field of writing, in several Indonesian language competition activities such as synopsis, and storytelling at the Karanganom sub-district level last year, it needs to be developed through a learning process that can improve writing skills. This research is aimed at writing skills with a contextual approach. Based on these problems, the research objectives to be achieved are: to improve writing skills with a contextual approach to Class V students of State Elementary School 2 Jambeyan Karanganom District Klaten Regency. The results of this study indicate an increase in students' writing skills with a contextual approach. This can be seen from the classical completeness percentage increased from pre-cycle of 23.08% to 61.54% in the first cycle and increased again in the second cycle to 84.62%.